Penerapan Metode SQ3R untuk Meningkatkan Kemampuan Pemahaman Teks Bacaan Siswa Kelas IV SDN 13 Gresik - Yunita, Nourma (DIDAKTIKA : Jurnal Pemikiran Pendidikan, 2026)
This study aims to evaluate the effectiveness of using the SQ3R method by fourth-grade students at SDN 13 Gresik in improving students' text comprehension skills. The background of this research is the low reading and comprehension abilities among students, particularly in recognizing main ideas, important details, as well as the ability to summarize information. This study uses a classroom action research (CAR) design implemented in two cycles, with the subject being fourth-grade students. There are 19 students involved in this study. The data collection methods are tests and observations, and the data analysis methods are quantitative and qualitative descriptive analysis. The research instruments consist of reading comprehension tests, observation sheets, and documentation. The results indicate that the SQ3R method is effective in enhancing the reading comprehension skills of fourth-grade students at SDN 13 Gresik. The class average score increased from 69.78 in the first cycle to 76.51 in the second cycle. The students' mastery level also increased, from 52.63% in the first cycle to 84.21% in the second cycle. Improvements can be seen from the average reading comprehension test scores in each cycle, as well as the increased participation of students in reading activities. Therefore, the SQ3R method is proven to be effective as a strategy in teaching reading, helping students understand texts more deeply and systematically.